Corporate bonds issues during anti-crisis actions by the European Central Bank after 2008 - Czaja, Jarosław (Emisje obligacji korporacyjnych w okresie działań antykryzysowych Europejskiego Banku Centralnego po 2008 roku, 2020)
The aim of the article is to determine whether the anti-crisis measures of the European Central Bank are conducive to increases in corporate bonds issues. This matter is important because it relates to a period when a very active monetary policy was applied, not only in the euro area countries. The internationalization of the debt markets increased the possibilities of indebtedness in the financial markets, with the excessive risk of the mass insolvency of various enterprises and even countries. The author points out that the actions of the European Central Bank have significantly changed the terms of issuing corporate bonds. The conclusions of this study are based on a comparative analysis of the volume of bond issues (with interest rates correlations), changes in ratings, and the impact of central bank intervention on the corporate bond market, mainly in the euro area and the USA. Additionally, debt sector indices (government, financial and corporate) were used. The time series mainly cover the period 2011-2019, but some figures come from earlier times. Central bank interventions in the bond markets (mainly the purchase of corporate bonds) increased corporate bond issues and shifted funding from loans to bond issues as other sectors slightly reduced the use of this type of deb
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 12, s. 31-46